Giraffa camelopardalis_heart_70% - Lauridsen, Henrik; Hansen, Kasper; Nørgård, Mathias Ø.; Wang, Tobias; Pedersen, Michael (Dryad Digital Repository, 2016)
Ready to 3D print STL file of Giraffa camelopardalis heart.